Part I: an Investigation of Calcitroic Acid and Its Phase II Conjugates. Part II: Toward the Development of a Novel Orally-available Asthma Treatment Targeting Gabaa Receptors in the Lungs - (:unkn) unknown (My University, 2019)
PART I Calcitroic acid (CTA) was isolated and characterized more than four decades ago.5 Radiolabeled calcitriol (1,25-dihydroxyvitamin D3) was used at that time to enable the identification of radioactive CTA formed in vivo, which was subsequently extracted and characterized by derivatization.7 CTA was found to be predominantly formed in the liver and secreted into the gut through the bile duct via enterohepatic circulation, leading to fairly high concentrations of this metabolite of vitamin D in the intestine.8 However, assuming it was only a catabolic product of calcitriol, it was ignored thereafter. Recently, novel experiments showed that CTA can bind the vitamin D receptor (VDR) and initiate gene regulation of certain metabolic enzymes.4 The VDR is a nuclear hormone receptor and is present in many tissues.9 VDR is a biological sensor with the ability to bind several endogenous ligands. Calcitriol has the highest known affinity for VDR and has been very thoroughly investigated. In contrast to that, very little is known about the main final metabolite of vitamin D: calcitroic acid. Because its binding to VDR is weaker than calcitriol, it was presumed to be biologically inactive at the time of its discovery. Gene regulation in the presence of CTA has now been demonstrated in epithelia, keratinocytes, and prostate cancer cells.8 One assumed function of VDR in the intestine is the regulation of P450 enzymes. These are important enzymes for detoxification, especially with respect to harmful accumulation of toxic endogenous small molecules, such as lithocholic acid. Our hypothesis is that CTA regulates this process in conjunction with VDR for the purpose of preventing the development of inflammation-based gastrointestinal diseases such as irritable bowel syndrome, or even colorectal cancer. My research has been focused on producing CTA synthetically and testing its effects in vitro and in vivo. Due to it being unavailable for purchase at a reasonable price and the difficulty of its synthesis, much of my research was focused on modifying and optimizing a lengthy synthetic route to the final product. Secondarily, I generated 13C-labeled CTA to be used as an isotopic standard to enable the quantification of CTA in bodily fluids. Several proposed phase two conjugates of CTA and the recently discovered other final vitamin D metabolite calcioic acid were also synthesized following novel synthetic routes. We confirmed the binding between these analogs and VDR. The availability of CTA conjugates will support their quantification in vivo in future studies using LCMS/MS and MALDI-TOF/TOF. Additionally, VDR’s expression in leukocytes has shown immune suppression influence with calcitriol as its ligand. Studies with CTA and its conjugates also have indicated similar anti-inflammatory effects. Further studies will be conducted to determine whether CTA or its conjugates have any of the suspected detoxification properties in the gut. PART II The treatment and control of asthma remains a persistent modern clinical problem, despite being recognized for decades and occurrence across the globe.10 The central hallmarks of asthma are chronically inflamed airways, hypersensitivity to certain external stimuli, and obstruction of the airways.11 These characteristics lead to clinical features that include persistent cough, shortness of breath, wheezing, coughing, and chest tightness.12 Our laboratory, in collaboration with the Cook laboratory at UWM, is seeking an alternate therapy to combat multiple symptoms associated with living with acute asthma.1, 13 Currently available treatments have multiple factors that could be improved upon, from the imprecise dosages of treatment delivered via inhaler14 to the adverse side effects of systemically administered corticosteroids.15-19 A better asthma drug alternative would be orally administered to improve patient compliance and eliminate dosage irregularity. Furthermore, unwanted central nervous system effects should be avoided at all cost. Finally, the alternative drug should alleviate a full range of asthma symptoms, such as relaxing the smooth muscle constriction and decreasing inflammation in the airways, rendering combination treatments obsolete.20 Central to achieving those goals is a new therapeutic target for asthma, which is the family of gamma-aminobutyric acid A receptors (GABAAR). GABAARs are ligand-gated chloride ion channels, whose primary function is to regulate intracellular chloride concentrations, especially in neurons. The GABAARs consists of five subunits combined into a heteropentamer.21 In recent decades, the Cook group has introduced GABAAR ligands based on the imidazobenzodiazepine scaffold that are selective to certain subtypes of GABAARs.22 With recent confirmation that distinct populations of GABAAR subtypes are present in lung tissue, our collaboration is keen to develop molecules that can target these subtypes. Further investigations have shown that these ligands mediate distinct pharmacological properties including relaxation of airway smooth muscle and anti-inflammation. Proof of concept that GABAAR ligands can alleviate asthma symptoms was first shown with plant-based positive allosteric modulator honokiol by Munroe et al.23 Our group has since developed imidazobenzodiazepine-based compounds that target relevant GABAAR subtypes expressed in the lung with pronounced efficacy in several asthmatic mouse models.1, 13, 20, 24 Achieving targeted asthmatic relief with oral medication and thus eliminating the use of corticosteroids is seen as a significant step forward in asthma treatment. 1. Yu, O. B.; Arnold, L. A., Calcitroic Acid–A Review. ACS Chemical Biology 2016, 11 (10), 2665-2672. 2. Esvelt, R. P.; Schnoes, H. K.; DeLuca, H. F., Isolation and characterization of 1.alpha.-hydroxy-23-carboxytetranorvitamin D: a major metabolite of 1,25-dihydroxyvitamin D3. Biochemistry 1979, 18 (18), 3977-3983. 3. Onisko, B. L.; Esvelt, R. P.; Schnoes, H. K.; DeLuca, H. F., Metabolites of 1 alpha, 25-dihydroxyvitamin D3 in rat bile. Biochemistry 1980, 19 (17), 4124-30. 4. Teske, K. A.; Bogart, J. W.; Sanchez, L. M.; Yu, O. B.; Preston, J. V.; Cook, J. M.; Silvaggi, N. R.; Bikle, D. D.; Arnold, L. A., Synthesis and evaluation of vitamin D receptor-mediated activities of cholesterol and vitamin D metabolites. European journal of medicinal chemistry 2016, 109, 238-46. 5. Pike, W. S., N. K., In Vitamin D, 2005; Vol. 2nd Ed. 6. Trends in Asthma Morbidity and Mortality. . Services., A. L. A. E. S. U. R. a. P., Ed. 7. Pascual, R. M.; Peters, S. P., Airway remodeling contributes to the progressive loss of lung function in asthma: an overview. The Journal of allergy and clinical immunology 2005, 116 (3), 477-86; quiz 487. 8. Moorman, J. E.; Rudd, R. A.; Johnson, C. A.; King, M.; Minor, P.; Bailey, C.; Scalia, M. R.; Akinbami, L. J., National surveillance for asthma--United States, 1980-2004. Morbidity and mortality weekly report. Surveillance summaries (Washington, D.C. : 2002) 2007, 56 (8), 1-54. 9. Forkuo, G. S.; Nieman, A. N.; Yuan, N. Y.; Kodali, R.; Yu, O. B.; Zahn, N. M.; Jahan, R.; Li, G.; Stephen, M. R.; Guthrie, M. L.; Poe, M. M.; Hartzler, B. D.; Harris, T. W.; Yocum, G. T.; Emala, C. W.; Steeber, D. A.; Stafford, D. C.; Cook, J. M.; Arnold, L. A., Alleviation of Multiple Asthmatic Pathologic Features with Orally Available and Subtype Selective GABAA Receptor Modulators. Molecular pharmaceutics 2017, 14 (6), 2088-2098. 10. Jahan, R.; Stephen, M. R.; Forkuo, G. S.; Kodali, R.; Guthrie, M. L.; Nieman, A. N.; Yuan, N. Y.; Zahn, N. M.; Poe, M. M.; Li, G.; Yu, O. B.; Yocum, G. T.; Emala, C. W.; Stafford, D. C.; Cook, J. M.; Arnold, L. A., Optimization of substituted imidazobenzodiazepines as novel asthma treatments. European journal of medicinal chemistry 2017, 126, 550-560. 11. Guidelines for the Diagnosis and Management of Asthma; National Heart, Lung, and Blood Institute: August 2007. 12. Cates, C. J.; Cates, M. J., Regular treatment with formoterol for chronic asthma: serious adverse events. The Cochrane database of systematic reviews 2012, (4), Cd006923. 13. Cates, C. J.; Cates, M. J., Regular treatment with salmeterol for chronic asthma: serious adverse events. The Cochrane database of systematic reviews 2008, (3), Cd006363. 14. Dahl, R., Systemic side effects of inhaled corticosteroids in patients with asthma. Respiratory medicine 2006, 100 (8), 1307-17. 15. Kelly, H. W.; Sternberg, A. L.; Lescher, R.; Fuhlbrigge, A. L.; Williams, P.; Zeiger, R. S.; Raissy, H. H.; Van Natta, M. L.; Tonascia, J.; Strunk, R. C., Effect of inhaled glucocorticoids in childhood on adult height. The New England journal of medicine 2012, 367 (10), 904-12. 16. Lipworth, B. J., Systemic adverse effects of inhaled corticosteroid therapy: A systematic review and meta-analysis. Archives of internal medicine 1999, 159 (9), 941-55. 17. Forkuo, G. S.; Nieman, A. N.; Kodali, R.; Zahn, N. M.; Li, G.; Rashid Roni, M. S.; Stephen, M. R.; Harris, T. W.; Jahan, R.; Guthrie, M. L.; Yu, O. B.; Fisher, J. L.; Yocum, G. T.; Emala, C. W.; Steeber, D. A.; Stafford, D. C.; Cook, J. M.; Arnold, L. A., A Novel Orally Available Asthma Drug Candidate That Reduces Smooth Muscle Constriction and Inflammation by Targeting GABAA Receptors in the Lung. Molecular pharmaceutics 2018, 15 (5), 1766-1777. 18. Olsen, R. W.; Sieghart, W., International Union of Pharmacology. LXX. Subtypes of gamma-aminobutyric acid(A) receptors: classification on the basis of subunit composition, pharmacology, and function. Update. Pharmacological reviews 2008, 60 (3), 243-60. 19. Sieghart, W.; Savic, M. M., International Union of Basic and Clinical Pharmacology. CVI: GABAA Receptor Subtype- and Function-selective Ligands: Key Issues in Translation to Humans. Pharmacological reviews 2018, 70 (4), 836-878. 20. Munroe, M. E.; Businga, T. R.; Kline, J. N.; Bishop, G. A., Anti-Inflammatory Effects of the Neurotransmitter Agonist Honokiol in a Mouse Model of Allergic Asthma. The Journal of Immunology 2010, 185 (9), 5586-5597. 21. Forkuo, G. S.; Guthrie, M. L.; Yuan, N. Y.; Nieman, A. N.; Kodali, R.; Jahan, R.; Stephen, M. R.; Yocum, G. T.; Treven, M.; Poe, M. M.; Li, G.; Yu, O. B.; Hartzler, B. D.; Zahn, N. M.; Ernst, M.; Emala, C. W.; Stafford, D. C.; Cook, J. M.; Arnold, L. A., Development of GABAA Receptor Subtype-Selective Imidazobenzodiazepines as Novel Asthma Treatments. Molecular pharmaceutics 2016, 13 (6), 2026-38.
Keywords: calcitriol; calcitroic acid; vitamin D receptor